92 Pasific boulevard - Macomber, Debbie; Mira Books (Don Mills, Ont : MIRA Books, 2009)
Sheriff Troy David had hoped to marry Faith Beckwith, but she's ended the relationship because of misunderstandings--inadvertently caused by Troy's daughter. However, Troy has plenty to keep himself occupied, like the unidentified remains found in a cave outside of town.
Adult.
Keywords: City and town life -- Fiction; Man-woman relationships -- Fiction; Sheriff -- Fiction